2007
DOI: 10.1126/science.1147614
|View full text |Cite
|
Sign up to set email alerts
|

LeuT-Desipramine Structure Reveals How Antidepressants Block Neurotransmitter Reuptake

Abstract: Tricyclic antidepressants exert their pharmacological effect -inhibiting the reuptake of serotonin, norepinephrine and dopamine -by directly blocking neurotransmitter transporters (SERT, NET and DAT, respectively) in the presynaptic membrane. The drug-binding site and the mechanism of this inhibition are poorly understood. We determined the crystal structure at 2.9 Å of the bacterial leucine transporter (LeuT), a homolog of SERT, NET and DAT, in complex with leucine and the antidepressant desipramine. Desipram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
364
4
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(399 citation statements)
references
References 22 publications
19
364
4
4
Order By: Relevance
“…Transporters for the amine neurotransmitters dopamine, norepinephrine, and serotonin are targets for important therapeutic agents and drugs of abuse, including antidepressants, cocaine, and amphetamines. The structural basis for the function of these proteins and their interactions with drugs has been a topic of intense recent interest (16,17).…”
mentioning
confidence: 99%
“…Transporters for the amine neurotransmitters dopamine, norepinephrine, and serotonin are targets for important therapeutic agents and drugs of abuse, including antidepressants, cocaine, and amphetamines. The structural basis for the function of these proteins and their interactions with drugs has been a topic of intense recent interest (16,17).…”
mentioning
confidence: 99%
“…Solute translocation is driven by a Na ϩ -and Cl Ϫ -dependent alternating access mechanism in which the proteins cycle through outwardly and inwardly facing conformations that bind and release substrates on opposite sides of the membrane (14). Major insights into structural mechanisms of NSS proteins have come from the homologous prokaryotic leucine transporter (LeuT) from Aquifex aeolicus, which has been crystallized in conformations corresponding to outwardly facing, occluded, inwardly facing, and inhibitor-bound forms (15)(16)(17)(18)(19)(20). These structures reveal that outwardly facing transporters possess an aqueously accessible external vestibule that opens to a compact central/primary substrate-binding site (S1) composed of residues from TM domains 1, 3, 6, and 8 (15).…”
mentioning
confidence: 99%
“…Earlier computational studies suggested that APC members possess the so called "5 ϩ 5"-fold (24), commonly found in the crystal struc-tures of several prokaryotic transporters belonging to evolutionary distinct protein families with different substrate specificities (25)(26)(27)(28). By using a sensitive homology threading approach, a three-dimensional model of PrnB was previously generated, using as template the crystal structure of the LeuT transporter of Aquifex aeolicus (23).…”
mentioning
confidence: 99%